Betaine chemistry, roles, and potential use in liver disease - Day, Christopher R.; Kempson, Stephen A. (Biochimica et biophysica acta, 2016)
Betaine is the trimethyl derivative of glycine and is normally present in human plasma due to dietary intake and endogenous synthesis in liver and kidney. Betaine is utilized in the kidney primarily as an osmoprotectant, whereas in the liver its primary role is in metabolism as a methyl group donor. In both organs, a specific betaine transporter mediates cellular uptake of betaine from plasma. The abundance of both betaine and the betaine transporter in liver greatly exceeds that of other organs. The remarkable contributions of betaine to normal human and animal health are summarized together with a discussion of the mechanisms and potential beneficial effects of dietary betaine supplements on liver disease. A significant amount of data from animal models of liver disease indicates that administration of betaine can halt and even reverse progression of the disruption of liver function. Betaine is well-tolerated, inexpensive, effective over a wide range of doses, and is already used in livestock feeding practices. The accumulated data indicate that carefully controlled additional investigations in humans are merited. The focus should be on the long-term use of betaine in large patient populations with liver diseases characterized by development of fatty liver, especially non-alcoholic fatty liver disease and alcoholic liver disease. •Betaine has several unique roles in animal and human health.•Most abundant in liver and is a methyl donor in one-carbon metabolism.•Betaine is used clinically to decrease homocysteine in plasma.•Alcoholic liver and non-alcoholic fatty liver are worldwide diseases.•Betaine alleviates most disturbances in rodent models of these diseases.